2019
DOI: 10.1080/13575279.2018.1555139
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Disclosure of Physical Abuse - The Process of Disclosing and the Responses from Social Welfare Workers

Abstract: Children experiencing physical abuse by their parents are left with several difficult decisions. The present study aims at exploring the process of disclosing the abuse and the responses from social welfare workers from a child perspective, in a Swedish context. Data was obtained from in depth interviews with 15 children with a history of child physical abuse. A qualitative content analysis was conducted in order to capture the children's experiences. Disclosing abuse was described as a process including sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
10
0
6
Order By: Relevance
“…Nevertheless, the main findings illustrated that from a highly selective sample of adolescents the process of disclosure and associated reactions, confirmed what has been reported from other studies on adolescents' abuse disclosures (e.g. Brennan & McElvaney, 2020;Cossar et al, 2019;Lemaigre et al, 2017;Thulin et al, 2020). Following Brennan and McElvaney's (2020) meta-analysis of qualitative studies on disclosures after abuse, the pressure cooker effect (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, the main findings illustrated that from a highly selective sample of adolescents the process of disclosure and associated reactions, confirmed what has been reported from other studies on adolescents' abuse disclosures (e.g. Brennan & McElvaney, 2020;Cossar et al, 2019;Lemaigre et al, 2017;Thulin et al, 2020). Following Brennan and McElvaney's (2020) meta-analysis of qualitative studies on disclosures after abuse, the pressure cooker effect (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies of adults with EDs admitted to residential treatment have also reported high rates of PTSD (Rienecke et al., 2020; Scharff et al., 2019). It is known that children and adolescents are more reluctant to disclose child maltreatment than adults given multiple fears of informing adults (Bottoms et al., 2016; Morrison et al., 2018; Thulin et al., 2019). They may not disclose until adulthood, if ever (Hunter, 2011; McElvaney, 2015), and delayed disclosure has been associated with higher rates of major depression and PTSD (Broman‐Fulks et al., 2007; Ruggiero et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The attitudes and the prevailing cultural beliefs on sexual abuse as well as having the structure and support to deal with the reported case are critical in changing behavior. Disclosure of abuse by the child is a complex process affected by the whole socio-ecological environment around the child; individual, family, school, community and cultural and societal attitudes (Alaggia, 2010;Thulin et al, 2019). Interventions, therefore, need to address the whole social ecology and should be coordinated and complementary.…”
Section: Discussionmentioning
confidence: 99%